PENGARUH KOMPETENSI DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PT BUSANA UTAMA TEXTILE (DEPARTEMEN SEWING) - Hasyim, Wachid; Rokhmatin, Isnaini (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
Human Resources is one of the most important factors in a company. It is not easy to find professional human resources to be a problem today. This is due to several factors including the level of competence and work stress that can affect employee performance. This study aims to analyze the competence and work stress on the performance of the employees of PT Busana Utama Tekstil (Sewing Department) Pekalongan. This type of research is quantitative. The population in this study were employees of PT Busana Utama Textile (Sewing Department) Pekalongan. The data were collected using saturated sampling sent to 60 respondents. The data techniques in this study were questionnaires and documentation with Multiple Linear Regression Analysis, with the help of SPSS 21 for windows software. The results showed that competence and work stress together have a significant effect on employee performance, indicated by the value of F count = 3.656> F table = 2.54 with a significance level of 0.032 <0.05. Likewise, the partial test (t test) for the competency variable (X1) obtained the value of t = 2.177> t table = 2,000 with a significance level of 0.034 <0.05, but there is a variable Job Stress (X2) which has no significant effect on employee performance by obtaining t count = 0.624 < t table = 2,000 with a significance level of 0.535 > 0.05. Meanwhile, the correlation between competence and work stress on employee performance obtained R2 value of 0.083 or 8.3% while the remaining 91.7% was carried out by other factors outside of the study. This the criteria for companies to be able to improve performance by making improvements continuously. so that it can have a positive impact on the company.